Accuracy of multi-experts' prioritization under Mallows' model of errors creation. Issue Volume 33:Issues 2(2021) (8th June 2021) - Marmor, Yariv N.; Gadrich, Tamar; Bashkansky, Emil
Abstract: Prioritization is widely used in quality practice. Since the process is accompanied by unavoidable errors, in order to improve accuracy, prioritization is usually repeated by M independent experts, followed by aggregation of their decisions. The article studies the bias of such a procedure, under the assumption of a "gold standard" existence and Mallows' model of errors creation, for different combinations of M, number of alternatives— n and probability of error-free prioritization P 0 . Thereby it becomes possible to know how many experts are required and how accurate must they be in order to prevent the bias from exceeding some threshold.